2019
DOI: 10.1002/jcop.22303
|View full text |Cite
|
Sign up to set email alerts
|

An ecological investigation of resilience among rural‐urban migrant adolescents of low socioeconomic status families in China

Abstract: The present study aims to explore the mechanism of resilience among rural‐urban migrant adolescents of low socioeconomic status (SES) families in China with the ecological system perspective. Selecting 946 rural‐urban migrant adolescents from the China Education Panel Survey, we used latent class analyses to distinguish different levels of resilience among migrant adolescents from low‐SES families, and logistic regressions to identify factors associated with resilience and to examine the cumulative risk and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 59 publications
(100 reference statements)
0
19
0
Order By: Relevance
“…It has also been found that an adolescent with inadequate family economic conditions has a lower level of resilience (Myers and Taylor, 1998 ). Some researchers believe that family SES affects resilience through the relationship between adolescents and their parents (Mackay, 2003 ; Gao et al, 2020 ; O'Gara et al, 2020 ). For example, parental confidence in the future of an adolescent may infuse them with high hopes, optimism, and a sense of direction, which further promotes their positive adaption during stressful situations (Gao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been found that an adolescent with inadequate family economic conditions has a lower level of resilience (Myers and Taylor, 1998 ). Some researchers believe that family SES affects resilience through the relationship between adolescents and their parents (Mackay, 2003 ; Gao et al, 2020 ; O'Gara et al, 2020 ). For example, parental confidence in the future of an adolescent may infuse them with high hopes, optimism, and a sense of direction, which further promotes their positive adaption during stressful situations (Gao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers believe that family SES affects resilience through the relationship between adolescents and their parents (Mackay, 2003 ; Gao et al, 2020 ; O'Gara et al, 2020 ). For example, parental confidence in the future of an adolescent may infuse them with high hopes, optimism, and a sense of direction, which further promotes their positive adaption during stressful situations (Gao et al, 2020 ). However, research has found that Chinese parents with low SES are typically so busy working that they seldom communicate with their children (Huang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study has found that cross-hukou-location friendship might be a resilient factor for non-local students. Therefore, a perspective of strength and resilience could be adopted to a greater degree by future studies to examine the protective factors of migrant children’s psychosocial integration (Gao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In CEPS, the adolescents’ psychological symptoms were evaluated by 10 items about dispirited, not concentrating, unhappiness, meaningless, no energy, sadness, nervous, worried, afraid, hunching bad things, not concentrating on class, which was widely used in previous studies [ 25 , 26 , 27 , 28 , 29 ]. A 5-point scale from 1 (never) to 5 (always) was used to grade each psychological symptom, and the total scores were ranged from 10 to 50, which the higher score indicated more severe psychological symptoms.…”
Section: Methodsmentioning
confidence: 99%